Stability of a sweet product of tamarillo (Cyphomandra betacea) preserved by combined methods - Villegas-Ruíz, Xadeni (2013)
The aim of this study was the use of the hurdle technology for preparing a sweet product (SPT) of tamarillo (Cyphomandra betacea) and assess its storage stability. SPT was prepared at the fruit natural pH (3.72), lowering the water activity (aw) (0.901) by adding sucrose and sodium benzoate (0.1%) as antimicrobial. SPT was stored under refrigeration (4 °C) conditions protected from light and it was analyzed every third day for 60 days. Physicochemical (color, aw, pH, and titratable acidity as citric acid), antioxidant (antioxidant capacity, total phenolics, and anthocyanins), and microbiological (aerobic mesophilic bacteria, molds, and yeasts), were determined. SPT was mixed with plain yogurt to evaluate the overall sensory acceptance during storage. The evaluation took place every seventh day during 49 days. The storage time had no effect neither on aw, pH or acidity of the SPT. It was observed an increase in the net change of color (0 to 4.9) and a decrease in total phenolic compounds (1.213-0.816 mg gallic acid/g SPT), total monomeric anthocyanins (0.910-0.611 mg cyanidin-3-glucoside/g SPT g), and antioxidant capacity (5.816-3.576 μmole Trolox/g SPT). The aerobic mesophilic bacteria (< 10 to 110 CFU/g), molds (< 10 to 380 CFU/g), and yeast (83 CFU/g) increased slightly during storage. The acceptance values of the sensory evaluation did not change significantly (p > 0.05) during storage.